A Theoretical Model of The Antecedents and Consequences of Employee Engagement: Dubin’s Method - R, Dr. Monica; R, Dr. Krishnaveni (Journal of Contemporary Research in Management (JCRM), 2022)
The quality of an organization’s human resources is perhaps the leading indicator of its growth and sustainability. The attainment of a workplace with high-caliber employees starts with the selection of the right people for the right jobs. This paper proposes a theoretical model of the antecedents and consequences of employee engagement (EE) using Dubin’s theory-building methodology. This paper has identified the work environment, perceived organizational support, supervisor support, rewards, recognition, and core self-evaluations as the major antecedents of EE. This paper further proposes job demands and resources as moderators of employee engagement. Hence, the purpose of the study is to propose a theoretical model of antecedents and consequences of engagement by incorporating the link between the antecedents(work environment, perceived organizational support, supervisor support, rewards, recognition, core-self evaluations), outcomes (employee performance and organizational citizenship behavior) and moderators(job demands and job resources) of employee engagement.